Upaya Meningkatkan Kesadaran Masyarakat terhadap Hipertensi dan Pencegahannya pada Komunitas Lanjut Usia - Alexander Halim Santoso; Triyana Sari; Joshua Kurniawan; Fernando Nathaniel; Brian Albert Gaofman; Geoffrey Christian Lo; I Made Satya Pramana Jaya (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
World Health Organization (WHO) approximates 1.28 billion individual suffers hypertension, with 46% of them does not realize it, and only 1 of 5 hypertensive individual has their blood pressure controlled. Hypertension prevalence is still relatively high in the elderly population who live in nursing home. This is one of the main health adversities that often happens and should not be underestimated due to its risk of complications. Uncontrolled blood pressure is one of the main risk factor to the global disease burden and total of global death, contributing up to 9,4 millions of deaths (8,5% of the global total) annually. This activity aims to increase the knowledge of the community about hypertension in elderly who lives in nursing home to increase the quality of life and reducing the cost burden of therapies and treatments. We use PDCA activity method to ensure the program could run smoothly and efficiently. This activity included 34 elderly respondents of the St Fransiscus Community with the mean age of 4 (11,8%) years. We found that 4 (11,8%) of the respondents have uncontrolled blood pressure. With the implementation of this program, it is hoped that the public awareness of elderly hypertension and its prevention is increased, so that there will be increase of quality of life for the elderly in the future and relieving the economical burden.